Systematic literature review on self-management and exercise programme for older adults living with chronic knee pain - Sulaiman, Suliza (Panyapiwat Institute of Management, 2024)
Background: Chronic knee pain is a significant health problem that greatly impacts the quality of life among older adults, and its prevalence continues to worsen annually. While various intervention programmes have been designed for chronic knee pain patients, only a few have evaluated the effectiveness of programmes supported by technology. Objective: The aim of this review is to identify current evidence regarding technology- based intervention programmes among older adults living with chronic knee pain. Methods: Keywords and subject headings were technology- based, intervention programme, chronic knee pain, and older adults. Between July and October 2023, a search was conducted on PubMed, SCOPUS, EDS, ProQuest, Cochrane Library, Google Scholar, and 'grey literature'. Papers were screened by four reviewers according to predetermined inclusion and exclusion criteria, and reference lists were reviewed for additional paper inclusion. Results: Four experimental randomized controlled trials with various randomisation procedures obtained. Two studies utilized web- based, one mobile apps, and one telerehabilitation. Furthermore, two trials did not blind participants, investigators, or outcome analysers to the intervention, despite differences in treatment between groups. The findings suggested that all self-management and exercise interventions appeared to be beneficial to older adults living with chronic knee pain, but the long- term effects were not clear. Conclusion: Research on technology-based interventions for chronic knee pain self-management and exercise programmes is progressing, but its significant effect on pain outcomes in older adults requires further experimental study. Nevertheless, the constraints of this review stem from the brief and restricted search time.